2011
DOI: 10.1182/blood-2011-02-337097
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo expansion of human Tregs specific for alloantigens presented directly or indirectly

Abstract: IntroductionRegulatory T cells (Tregs) play a dominant role in transplantation tolerance, as shown by adoptive cell transfer for the prevention of organ graft rejection and GVHD in experimental models. [1][2][3][4][5][6] Translating Treg therapies to humans requires cell isolation and purification, because transfer of the accompanying effector T cells would exacerbate rather than ameliorate human disease. Naturally occurring Treg populations comprise 1%-3% of the human T-cell repertoire. 7 Tregs are characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
109
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(115 citation statements)
references
References 47 publications
5
109
1
Order By: Relevance
“…However, the expansion of thymus derived Treg cells and the generation of polyclonal in vitro-induced Treg (iTreg) cells from naive cells have the disadvantage that these cells are expanded/generated from an existing pool, and have a broad rather than a selective reactivity towards alloantigens. Thus, the use of allospecific Treg cells has the advantage of avoiding broad immune suppression as suggested by Anasetti's group [33]. Moreover, the polyclonal expansion obtained by simply using CD3/CD28 beads risks the expansion of other possible auto-reactive cells.…”
mentioning
confidence: 99%
“…However, the expansion of thymus derived Treg cells and the generation of polyclonal in vitro-induced Treg (iTreg) cells from naive cells have the disadvantage that these cells are expanded/generated from an existing pool, and have a broad rather than a selective reactivity towards alloantigens. Thus, the use of allospecific Treg cells has the advantage of avoiding broad immune suppression as suggested by Anasetti's group [33]. Moreover, the polyclonal expansion obtained by simply using CD3/CD28 beads risks the expansion of other possible auto-reactive cells.…”
mentioning
confidence: 99%
“…Selection and use of antigen-specific Treg has been proposed to improve Treg therapeutic efficiency and lower the risk for unwanted nonspecific immune suppression caused by transferring large numbers of polyclonal Treg (Koenecke et al 2009;Hall et al 2009;Peters et al 2008;Veerapathran et al 2011). Recent studies have shown that ex vivo expanded alloantigen specific Treg obtained enhanced suppressive capacity in allogeneic responses in vitro (Peters et al 2008;Golshayan et al 2007) and were more potent than polyclonal Treg in protecting against alloimmune-mediated injury of human skin grafts in a humanized mouse model (Yamano et al 2011;Sagoo et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This finding may also explain the observation that a simultaneous influx of both Ag-specific effector T cells and Tregs is observed after s.c. purified protein derivate injection (69). Expansion of alloantigen-specific Tregs through stimulation with other cell types like PBMCs (18,19) and B cells (10,20) has been documented previously. Our results with PBMCs as allogeneic stimulator cells for nTreg expansion are in line with previous publications, and relatively high stimulator/Treg ratios in combination with IL-2 and IL-15 are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Results from animal studies indicated that DCs can be used to expand alloreactive Tregs (27)(28)(29). Human immature DCs can stimulate the expansion of Tregs (19), but some degree of maturation leading to semimature DCs (30) yielded better results. In all protocols, there is a need for exogenous IL-2 to obtain optimal Treg expansion, but the requirements for exogenous cytokines may be different when mature monocyte-derived DCs (moDCs) are used as stimulator cells (31).…”
mentioning
confidence: 99%
See 1 more Smart Citation